Critical Factors Impacting the Implementation of Environmental Protection Strategies among Malaysia Industries - Sarwar, Abdullah; Azam, S. M. Ferdous; Khan, Nasreen; Raman, Murali; Seng, Vincent Oh Kim; Siddika, Aysa (International Journal of Energy Economics and Policy, 2023)
Environmental protection is a heavily debated topic along with development. Uncontrolled development will sacrifice our environmental and causing issues such as pollution, land slide, flash flood, etc. The objective of this study is to understand drivers of the implementation of environmental protection strategy among industries in Malaysia. Questionnaire was designed and tested with 130 Malaysian organizations. The framework consisted of independent variables such as Client’s Requirement, Corporate Social Responsibility, Government Grants and Subsidy versus the dependent variable Environmental Protection Strategy. From the Exploratory Factor Analysis (EFA), it was found out that only client’s requirement and corporate social responsibility are relevant towards implementation of environmental protection strategy. One of the important findings is that government regulation is no longer a mandatory driver for organizations to implement environmental protection strategy. This could be a positive sign that organizations are working the self-regulatory direction than instrumental enforcement. This is in par with department of environment’s latest focus to implement guided self-regulation through environmental mainstreaming tools. The outcome of the study can help the policy makers, regulatory bodies, and non-government organizations (NGOs) to shape their direction to form strategies that are most effective.